Photosensitization Induced by Heterophyllaea pustulata in Goats: Sequential Development of Skin Lesions - Micheloud, Juan Francisco; Lujan, Lluís; Colque Caro, Luis Adrián; Núñez-Montoya, Susana C.; Barbeito, Claudio Gustavo; Portiansky, Enrique L.; Gimeno, Eduardo Juan (Sage Publishers, 2021)
Five adult Saanen goats received a single oral dose of Heterophyllaea pustulata containing 42.25 μg/kg rubiadin (anthraquinone) and 3 adult goats were untreated controls. All goats were exposed to sunlight and sequential ear skin biopsies were collected before treatment and at 32 hours, 3 days, 8 days, and 15 days after treatment. Changes at 32 hours after dosing included epidermal spongiosis, single cell death and acantholysis, an increased BAX/BCL-2 protein ratio, and dermal edema. Lesions at day 3 included epidermal and adnexal necrosis, crust formation, and acanthosis. Acanthosis, hyperkeratosis, and dermal fibrosis and neovascularization were present at day 15. The pro-apoptotic (BAX)/anti-apoptotic (BCL-2) protein ratio increased at 32 hours, whereas epidermal and dermal PCNA immunolabeling increased between days 8 and 15 after treatment. The cutaneous lesions were consistent with sunlight-induced damage, and the occurrence in treated but not control goats indicates photosensitization.